Lhe Balance Ofpower in South America: Lhe Discourse of the Intellectuals and Its Causal Configurations (1832-1881) - Garay-Vera, C; Elgueta-Rosas, R (ASOC ESPANOLA CIENCIA POLITICA & ADM-AECPA, 2023)
The boundaries controversies in the Southern Pacific impacted on the theoretical and empir-ical discussion about uti possidetis juris during the 19th century sustained by the foreign policy decision - makers of Argentina, Bolivia, Chile and Peru, which were also some of their most prominent public intellectuals. Thus, our main objective is to assess the aforementioned deci-sion - makers theses in order to elucidate why the same arguments had given different solu-tions. Thereon, the method that we utilize is the fuzzy sets qualitative comparative analysis (fsQCA) to assess the ideas of the above - mentioned intellectuals that are contained in their respective publications. As preliminary result, we argue that the perceived uncertainty of the decision - maker about a particular solution is a necessary and sufficient cause for the absence of war. Our main finding is that, unlike the perceived uncertainty of alternative solutions to war, or the perceived uncertainty of alternative solutions to war, perceptions about regional balance of power are not relevant to achieve pacific solutions to international controversies.